COVID-19 pandemic, medical attention, and self-care of patients with type 2 diabetes at a Peru-based hospital: An analytical cross-sectional study - Calderón-Ticona, Jorge (2023)
“Background: To determine the association between coronavirus disease-2019 (COVID-19), medical attention and self-care of patients with type 2 diabetes (T2DM) at the Archbishop Loayza National Hospital. Methods: This analytical cross-sectional study, involved interviewing 181 T2DM patients and recording their actions regarding three aspects–self-care measures, medical care, and spending on medicines–before and during the pandemic. The relationships between the variables were established using descriptive and analytical statistics. Results: During the pandemic, self-care decreased to 37%; 26% had access to medical care. Patients in the provinces experienced better self-care (Lima: 35%; Provinces: 61%; p=0.002). Patients with comorbidities also took good care of themselves (with comorbidities: 41%; without comorbidities: 29%; p=0.036). Conclusions: COVID-19 had a negative influence on T2DM patients regarding self-care and medical care. One out of four patients received medical care. Additionally, being outside Lima and having comorbidities were associated with better self-care during the pandemic.“